Risk communication by community health agents in the prevention of COVID-19 - Muñoz, Rilva Lopes de Sousa; Valério, Lilyanne Barboza de Oliveira (Seven Editora, 2023)
Unsuccessful prevention of the disease caused by the new coronavirus (COVID-19) can only be possible if everyone is willing to do their part, which has become a critical issue in facing the pandemic caused by this emerging virus. With the permanence of its circulation in the population after three years of the pandemic, prevention must also be permanent. This prevention must be centered on risk communication and community participation through popular health education. The object of the theoretical review and appreciation of this chapter focuses on the link between the concept of popular health education for communities, risk communication during health crises, such as the COVID-19 pandemic, and the role of the Community Health Agent (CHA) in this process. The CHA is the character of primary health care with greater capillarity, going from house to house, being able to disseminate information and develop knowledge in health, advising on preventive measures through a language of the community, based on scientific knowledge, but not laden with useless complexities for that target audience. Therefore, it is necessary to periodically train these very potential workers and, although the Health with Agent Program is in progress, it will bring future results with a generation of CHAs that are more prepared to carry out their attributions in critical moments of other epidemics that may arise. They need up-to-date specific actions of permanent education, being carried out promptly so that the communication practice is effective and quick in promoting equity in health in the Brazilian population. DOI:https://doi.org/10.56238/emerrelcovid19-014